KARAKTERISTIK RAGAM GERAK DAN TATA RIAS-BUSANA TARI NGREMO SEBAGAI WUJUD PRESENTASI SIMBOLIS SOSIO KULTURAL - Wahyudiyanto - (FBS UNY, 2006)
Ngremocourse, the theme of the dance is moving from ritual to political one so that thepresent growth looks like soldier dance. The heroic value embodied in the dancetheme is identified as the spirit of struggle to get independence. The heroic themeis visualized in the dance movement, costume and makeup. In the movementaspect, the changes are from soft to fast speed, and supple to stiff moves. Thecostume is adopted from East Javanese prince's attributes worn in theindependence war. Ngremo dance, which spreads around Surabaya, thereforerepresents the imaginary figure of Cakraningrat and the gallant, authoritativeand resolute Sawunggaling.Key words: Ngremo, characteristic and heroicdance is presented to begin Ludruk performance. In its